(untitled) (Eurasian Journal of Ecology, 2023)
The findings of a study on the amount of heavy metals in the soils of a significant industrial area are presented in this scientific publication. Samples were collected in various contaminated locations of the city for chemical analysis: in the northern industrial zone, in the northeastern industrial zone, in the central residential zone, in the suburban zone. The contents of Zn, Pb, Cu, and Cd were determined in the prepared soil samples. Based on the results of chemical analysis, it was discovered that the average concentrations of the acid-soluble form of the studied heavy metals exceed the background values. The total reserve and physicochemical characteristics of soils determine the amount of acid-soluble heavy metals present in the soil. Thus, the maximum content of mobile heavy metals was discovered in the meadow-chernozem soil, and the minimum in the southern chernozems. A large mosaic content of heavy metals was revealed for the territory under consideration. On average, the acid-soluble heavy metals are characterized by zinc-cadmium geochemical specialization. It has been established that the soils of residential areas and the northeastern industrial zone are classified as medium pollution, the soils of the northern industrial zone are highly polluted, and the soils of the eastern outskirts are to an acceptable level of pollution. Key words: soil, heavy metals, environmental assessment, soil pollution.